Efektivitas E-Worksheet Terhadap Kemampuan Pemecahan Masalah Ditinjau dari Minat Belajar Siswa pada Materi Perbandingan - Betty Kusumaningrum; Ely Fauziah; Esti Harini (Universitas Sarjanawiyata Tamansiswa, 2022)
This study aims (1) to determine the differences in problem-solving abilities of students who learn to use e-worksheets and do not use e-worksheets (2) to determine differences in problem-solving abilities between students who have low, medium, and high interests (3) to find out whether there is an interaction or not between the use of e-worksheet in terms of learning interest on students' problem-solving abilities. This research is a quantitative study with a quasi-experimental with a non-equivalent control groups design. The subjects of this study were students of class VII B and VII C of SMP Negeri 4 Sewon with 30 students each. The technique of taking the subject is using cluster random sampling. The instrument used in this research is a questionnaire of students' interest in learning mathematics and a test of problem-solving abilities. Data analysis in this study used factorial design analysis of variance. The results of this study indicate that (1) there are differences in the problem-solving abilities of students who learn using e-worksheets and do not use e-worksheets, (2) there are differences between students who have an interest high, medium, and low learning on problem solving abilities, (3) there was no interaction between the use of e-worksheets in terms of interest in learning to ability In solving students' problem solving, the results of the analysis showed that the results were not significant.